Nível de atividade física, sono e qualidade de vida em pacientes com doença de Alzheimer - Stein, Angelica Miki [UNESP]; Costa, José Luiz Riani [UNESP]; Vital, Thays Martins [UNESP]; Hernandéz, Salma Stephany Soleman [UNESP]; Santos, Marcelo Garuffi [UNESP]; Teixeira, Camila Vieira Ligo [UNESP]; Stella, Florindo [UNESP] (My University, 2012)
Physical activity (PA) has been considered an important non pharmacological feature that provides benefi ts on sleeping and quality of life of patients with Alzheimer’s disease (AD). The aim of this research was to analyze the relation of the level of PA; sleep disturbances and quality of life in pacients with AD. The study included 30 patients with PA. To measure PA level, sleeping and quality of life, it was used, respectively: Modifi ed Baecke Questionnaire for the Elderly, Mini Sleep Questionnaire and Quality of life assessment scale on Alzheimer’s disease – answered by the patients and their caregivers. For comparçliing of sleeping and quality of life, the sample was divided into two groups (higher and lower PA levels). In order to verify relations between the variables, and for the comparison both groups, it was used, respectively: Spearman correlation and U-Mann Whitney tests. It was admitted the level of signifi cance at 5% for all analyzes. Patients had a low level of PA and it was only found relationship positive, moderated and signifi cant (rho = 0,4; p = 0,01) between the level of PA and the caregiver’s quality of life. Thus, the caregivers of more active patients have a better quality of life and, there were no diff erences in sleep and quality of life when comparing the lowest and the highest level of PA groups of patients with AD.

A atividade física (AF) tem sido considerada um importante recurso não farmacológico, que pode proporcionar benefícios ao sono e à qualidade de vida de pacientes com Doença de Alzheimer (DA). O presente estudo teve por objetivo analisar a relação entre nível de atividade física, distúrbios do sono e qualidade de vida em pacientes com DA. Participaram deste estudo 30 pacientes com DA. Para mensurar nível de AF, sono e qualidade de vida foram utilizados, respectivamente: Questionário Baecke Modifi cado para Idosos, Mini Questionário do Sono e Escala de avaliação da qualidade de vida na Doença de Alzheimer – respondida pelo paciente e cuidador. Para compara- ção do sono e da qualidade de vida, em função do nível da prática de AF, a amostra foi dividida em dois grupos (maior e menor nível de AF). Para verifi car relações entre as variáveis e comparar os grupos foram empregados, respectivamente, os seguintes testes: correlação de Spearman e o teste de U de Mann Whitney. Foi admitido o nível de signifi cância de 5% para as análises. Os pacientes apresentaram um baixo nível de AF e foi encontrada relação positiva, moderada e signifi cativa (rho = 0,4; p = 0,01) entre nível de AF e qualidade de vida do cuidador. Concluimos, assim, que cuidadores de pacientes mais ativos possuem uma melhor qualidade de vida e não existe relação entre sono e qualidade de vida e nível de AF de pacientes com DA.
Level of physical activity, sleep and quality of life of patients with Alzheimer’s disease
Keywords: Level of physical activity; Sleep; Quality of life; Alzheimer’s disease; Nível de atividade física; Sono; Qualidade de vida; Doença de Alzheimer